2018
DOI: 10.11604/pamj.2018.30.199.15656
|View full text |Cite
|
Sign up to set email alerts
|

The role of faith leaders in influencing health behaviour: a qualitative exploration on the views of Black African christians in Leeds, United Kingdom

Abstract: IntroductionBlack African communities in the U.K suffer from health disparities compared to the general population. This has been attributed to the lack of culturally sensitive interventions that are meaningful to them. Faith leaders are an integral part of the community and are known to have immense influence on health behaviour of congregants and community members. However, their role in health behaviour change (alcohol and tobacco use) has been largely neglected. The aim of this study is to explore the view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 28 publications
2
37
0
Order By: Relevance
“…Evidence from Uganda showed that teamwork between religious leaders and health administrators is vital for reducing misperception and false beliefs that may not actually be of the religion’s view, that in turn increase uptake of health services [ 54 ]. As a result, working closely with religious leaders may have positive outputs to increase accessibility and utilization of maternal health services [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from Uganda showed that teamwork between religious leaders and health administrators is vital for reducing misperception and false beliefs that may not actually be of the religion’s view, that in turn increase uptake of health services [ 54 ]. As a result, working closely with religious leaders may have positive outputs to increase accessibility and utilization of maternal health services [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, being a Muslim was found to be associated with less likelihood of engaging in more than one COVID-19 protective behaviour. Religious leaders have been esteemed as key stakeholders in health promotion, given the significant influence they have on their followers, thus making religion a key factor in the adoption or rejection of health behaviours (Lumpkins et al 2013;Anshel and Smith 2014;Heward-Mills et al 2018). The activities of some religious sects have been found to be inimical to the containment of the current coronavirus pandemic in different countries.…”
Section: Discussionmentioning
confidence: 99%
“…9 Because FBOs are embedded in the communities they serve, they can reach a range of groups with FP and reproductive health messages that are shaped by local cultures and beliefs and also provide services. [10][11][12] Because faith influences health care beliefs and behaviors, religious leaders can influence healthseeking behaviors 4,5 and their support of FP can increase its uptake. 6 An evaluation of the Nigeria Urban Reproductive Health Initiative found that contraceptive uptake was 1.7 times higher for women exposed to FP messages from religious leaders than among women who were not, a statistically significant difference.…”
Section: Expanding the Role Of Faith-based Organizations In Family Planning Advocacymentioning
confidence: 99%